Effect of Robot-Assisted Training on Unilateral Spatial Neglect After Stroke: Systematic Review and Meta-Analysis of Randomized Controlled Trials - Bazan, Rodrigo [UNESP]; Fonseca, Bruno Henrique de Souza; Miranda, Jessica Mariana de Aquino; Nunes, Hélio Rubens de Carvalho [UNESP]; Bazan, Silméia Garcia Zanati [UNESP]; Luvizutto, Gustavo José (SAGE Publications, 2022)
Background: Several studies have shown that robotic devices can effectively improve motor function in stroke patients through limb activation. However, the effects of robot-assisted therapy on perceptual deficits after stroke is unclear. Objective: This review aimed to evaluate the effectiveness of robotic limb activation in patients with unilateral spatial neglect (USN) after stroke. Methods: In this systematic review, a literature search was performed using MEDLINE, EMBASE, CENTRAL, CINAHL, and LILACS databases without language restrictions. Randomized controlled trials (RCTs) and quasi-RCTs of robot-assisted therapy for USN after stroke were selected. Two reviewers independently assessed the risk of bias and certainty of the evidence of the included studies. Results: A total of 630 studies were identified, including five studies for qualitative synthesis and four meta-analyses. The results of RCTs comparing robotic limb activation with a control group suggested an improvement in the degree of USN measured by the line bisection test (standardized mean difference [SMD], −0.64; 95% confidence interval [CI], −1.13 to −0.15; P =.01). There were no differences between the groups in the motor-free visual perception test 3rd edition (SMD, 0.27; 95% CI, −0.25–0.79; P =.31), star cancellation test (SMD, 0.26; 95% CI, −0.42−0.94; P =.54), Albert’s test (SMD, −0.67; 95% CI, −2.01−0.66; P =.32), and Catherine Bergego Scale (SMD, −0.81; 95% CI, −2.07−0.45; P =.21). Conclusion: The study demonstrated that limb activation through robotic therapy can improve midline perception. However, there was no impact on tasks assessing visual scanning, functionality, or activities of daily living.
Keywords: limb activation; robot-assisted therapy; stroke; unilateral spatial neglect